Generation of 1.55 micron pulsed fibre laser using graphene oxide and zinc oxide as a saturable absorber / Nur' Afiqah Abdul Aziz - Nur' Afiqah, Abdul Aziz (2019)
This research work aims at exploring various new materials for saturable absorber (SA) application in generating Q-switching pulses train operating at 1.5 μm region. These nanomaterials are graphene oxide (GO) and zinc oxide (ZnO). The fibre lasers employ Erbium-doped fibre (EDF) as an amplification medium. Firstly, passive Q-switched Erbium Doped Fibre Lasers (EDFLs) have been successfully demonstrated using the newly developed GO film based SAs based on two different host polymers; Poly (Vinyl alcohol) (PVA) and Poly (Methyl methacrylate) (PMMA). The GO material was obtained through chemical oxidation of graphite. By incorporating GO PMMA SA into an EDFL set up, sturdy Q-switched pulses train were generated to operate in a wavelength of 1531.6 nm as the pump power being tuned within vary of 11.8 to 83.0 mW. The repetition rate was tunable within 21.5 kHz to 68.7 kHz. The maximum pulse energy of 145 nJ and the minimum pulse duration of 6.12 μs were obtained at the pump power of 83.0 mW. The research proceeds with the GO PVA SA, where the Q-switched was realized with the repetition rate tunable from 32.45 kHz to 81.7 kHz. At the maximum pump, the highest single pulse energy and repetition rate of 109.30 nJ and 81.7 kHz were achieved. These results show that GO PMMA film operate excellent than PVA film in terms of operating pump power range and pulse energy. Later, two Q-switched EDFLs were also proposed and demonstrated using a ZnO based SA. It is worthy to note that the EDFL produces a stable Q-switched pulses train with a higher pulses energy when the polymer material was replaced from PMMA to PVA. The ZnO PVA film-based Q-switched laser operated at 1560.4 nm within the 980nm pump power range from 11.8 mW to 77.9 mW. At 77.9 mW pump power, the laser showed the repetition rate, pulse energy, and pulse duration of 61.43 kHz, 154.6 nJ, and 7.00 μs, respectively. These results show that both GO and ZnO materials have new potential for application in pulsed laser generation.